Provable multiple replication data possession with full dynamics for secure cloud storage. (25th June 2015) - Zhang, Yafang; Ni, Jianbing; Tao, Xiaoling; Wang, Yong; Yu, Yong
Summary: Cloud storage has been gaining tremendous popularity among individuals and corporations because of its low maintenance cost and on‐demand services for the clients. To improve the availability and the reliability of critical data, storing multiple replicas on multiple servers is a commonly used strategy. Currently, several provable data possession (PDP) protocols for multiple replicas of dynamic data have been proposed to ensure the integrity of outsourced multi‐copy data, but the efficiency of these protocols on verifying multiple replicas one by one is not satisfactory. In this paper, we propose a provable multiple replication data possession protocol with full dynamics, named MR‐DPDP. In MR‐DPDP, we utilize a novel authenticated data structure called Merkle hash tree with rank to support both full dynamic data updates and efficient integrity verification. In addition, our construction with RSA signature can support both variable‐sized file blocks and public verification. Through security proof and performance evaluation, we demonstrate that MR‐DPDP not only is sound but also incurs less communication overhead when updating data blocks as well as verifying a proof of the integrity of multiple replicas. Copyright © 2015 John Wiley & Sons, Ltd.